Referral for specialist follow-up and its association with post-discharge mortality among patients with systolic heart failure (from the National Heart Failure Audit for England & Wales) - Emdin, C; Hsiao, A; Kiran, A; Conrad, N; Salimi-Khorshidi, G; Woodward, M; Anderson, S; Mohseni, H; McMurray, J; Cleland, J; Dargie, H; Hardman, S; et al. (Elsevier, 2017)
For patients admitted with worsening heart failure, early follow-up after discharge is recommended. Whether outcomes can be improved when follow-up is done by cardiologists is uncertain. We aimed to determine the association between cardiology follow-up and risk of death for patients with heart failure discharged from hospital. Using data from the National Heart Failure Audit (England & Wales), we investigated the effect of referral to cardiology follow-up on 30-day and one-year mortality in 68 772 patients with heart failure and a reduced left ventricular ejection fraction (HFREF) discharged from 185 hospitals between 2007 to 2013. The primary analyses used instrumental variable analysis complemented by hierarchical logistic and propensity matched models. At the hospital level, rates of referral to cardiologists varied from 6% to 96%. The median odds ratio (OR) for referral to cardiologist was 2.3 (95% confidence interval [CI] 2.1, 2.5), suggesting that, on average, the odds of a patient being referred for cardiologist follow-up after discharge differed approximately 2.3 times from one randomly selected hospital to another one. Based on the proportion of patients (per region) referred for cardiology follow-up, referral for cardiology follow-up was associated with lower 30-day (OR 0.70; CI 0.55, 0.89) and one-year mortality (OR 0.81; CI 0.68, 0.95) compared with no plans for cardiology follow-up (i.e., standard follow-up done by family doctors). Results from hierarchical logistic models and propensity matched models were consistent (30-day mortality OR 0.66; CI 0.61, 0.72 and 0.66; CI 0.58, 0.76 for hierarchical and propensity matched models, respectively). For patients with HFREF admitted to hospital with worsening symptoms, referral to cardiology services for follow-up after discharge is strongly associated with reduced mortality, both early and late. Key Words: Heart failure, follow up, specialist, instrumental variables, health services   In the United Kingdom’s healthcare system, cardiology care is generally provided by the hospitals and, hence, any policy recommendation for routine cardiology follow-up would have major resource and organisational implications for those hospital staff and payers not currently providing this component. We sought to assess this policy recommendation by investigating the effect of referral to cardiology follow-up on the risk of 30-day and one-year mortality in a large cohort of patients admitted for HFREF in England and Wales.